Problem based learning on creativity domain in problem solving for secondary school: A systematic literature review analysis - Jamal, Siti Najihah (EJMCM, 2020)
Problem-based learning (PBL) is one of the 21st century teaching and learning strategies in STEM education. STEM is an acronym for Science, Technology, Engineering and Mathematics. Ministry of education has found that PBL can be successfully applied to STEM field. PBL has the potential to develop creativity in problem solving and make students think creatively. It is also considered as an active learning method that encourages the students’ interest in understanding STEM concepts. Therefore, it is becoming a necessity to see how far the creativity domain in problem-based learning has been applied towards students especially in secondary school. Because there was lack of research about that. This systematic literature review analysis aims to focus on the similarities and differences such as the steps of problem-based learning applied, the creativity domain in problem solving, the findings of the study and the gap of research between all the articles. The study article was selected through a database of Scopus and Science Direct Journals according to keywords. Keywords used in the search are problem-based learning AND creative thinking AND secondary school. The search has been limited between 2009 until 2019. The thirteen of articles have been chosen to be analyzed based on the four steps in systematic literature review. The four steps included frame a question, run a search, the abstract and tittle of individual papers have to be read, and the information need to be abstract from selected set of final articles. The results reported the most suitable of creativity domain used in problem solving by the past researchers were fluency, flexibility, originality, elaboration and evaluation. However, generally the domain of creativity to be measured is not described in detail at every step of the problem-based learning even though problem-based learning strategy was very effective in improving students’ creative thinking.